2005
DOI: 10.1081/pte-200057818
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Electrical Properties of Natural Fiber: HDPE Composites

Abstract: The composites of banana, hemp, and agave with HDPE resin were separately prepared in different ratios, 60:40, 55:45, 50:50, and 45:55 (wt=wt). These fibers were also treated with maleic anhydride and the effect of maleic anhydride was studied on surface resistivity and volume resistivity of wood polymer composites. The surface resistivity decreases with an increase in fiber content in the composites, while volume resistivity increases. The maximum surface and volume resistivities were observed in untreated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
1
16
0
2
Order By: Relevance
“…Morphological observations confirmed that the removal of cementing agents from raw banana fibers enhanced the fiber adhesion properties with matrix. The electrical properties of banana and other natural fibers reinforced high density polyethylene composites have been studied and found that the untreated banana fiber showed better resistivity and volume resistivity while maleic anhydride treated agave fiber composites showed minimum surface resistivity and volume resistivity 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Morphological observations confirmed that the removal of cementing agents from raw banana fibers enhanced the fiber adhesion properties with matrix. The electrical properties of banana and other natural fibers reinforced high density polyethylene composites have been studied and found that the untreated banana fiber showed better resistivity and volume resistivity while maleic anhydride treated agave fiber composites showed minimum surface resistivity and volume resistivity 35 .…”
Section: Introductionmentioning
confidence: 99%
“…These composites can be used in different myriad fields from the residential buildings to aeronautic industries due to their low cost, biodegradability, ease of processing, and the absence of toxic byproducts . Other natural and wood fillers can be also treated to develop various polymer composites, for example, agro‐waste and maleic anhydride (MA) treated or maleated polymers (polystyrene, novolac, high density polyethylene, and cane bagasse‐melamine formaldehyde). On the other hand, the use of renewable, low price, and recycling waste resources in plastic composites is becoming more common .…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in the swelling of water was observed in the case of highly crystalline maleic anhydride treated or maleated PP and maleated wood flour composites having a high weight ratio of flour to PP . Other natural and wood fillers, which were treated to develop various polymer composites, for example, agrowaste based novolac and maleated polystyrene, high‐density polyethylene, and cane bagasse–melamine formaldehyde . The better crosslinking and uniform dispersion of filler in the PP matrix can be achieved by the surface treatment of the filler …”
Section: Introductionmentioning
confidence: 99%